Review of target objects for the group-operated unmanned aerial vehicles application - A. I. Selin; I. K. Turkin (Научный вестник МГТУ ГА)
Currently, the big number of companies, and specifically in Russia, is engaged in designing unmanned aerial vehicles (UAV). It is caused by the tendency to reduce human labor in various fields of activity, in particular, associated with a great risk to life and health. All these factors lead to the steady growth of different-type missions for the UAV application. Urgency of the research generates considerable interest towards the issues of the UAV application. As part of developing a method for determining UAV design parameters, the author analyzed the results in this domain, considering the operation in a group of aircraft. In order to propose a conceptual aircraft solution for designing a model, the analysis of target objects for the UAV group application was conducted. The article considers various target objects for the application of UAV groups. The result of the analysis for target objects can form the basis for the conclusion involved with the imposed requirements for the design of this UAV class. Compared to other specialists’ articles, this paper is distinguished by synthesizing the achievements in the sphere of group-operated UAV design, as well as by establishing the basic trends for their application while conducting warfare.